An experimental and numerical analysis of a novel water blind-Trombe wall system. (1st February 2020) - Hu, Zhongting; Zhang, Sheng; Hou, Jingxin; He, Wei; Liu, Xianghua; Yu, Cairui; Zhu, Jian
Highlights: A novel water blind-integrated Trombe wall (WBTW) was introduced. Numerical and experimental study of the WBTW with existing two walls. The WBTW system exhibited a quite satisfying insulation performance with the average heat transfer coefficient of 0.8 W/m 2 ·K. The WBTW system reduced the overall thermal load by up to 42.6% with an annual energy harvested of 435.7 kWh. Abstract: This research proposes a novel Trombe wall using blinds as the shading and simultaneously the water flowing channel (named WBTW), which renders the possibility of meeting the occupants' demands in different seasons, such as space heating, ventilating and domestic hot water. A dynamic coupled model of the WBTW system together with an experimental validation are implemented. The simulated results suggested that monthly average thermal efficiency of the WBTW system was ranged from 20% to 60% during non-heating season and 30%-50% during heating months. To determine the superb thermal performance of the WBTW system, comparison of the annual performance between the WBTW and two existing walls was implemented, including a traditional Trombe wall system (TW) and conventional wall system (CW). The most satisfying thermal insulation in summer were CW, WBTW and TW, in that order. In winter, the WBTW system displayed a pretty satisfying insulation level with the mean heat transfer coefficient of 0.8 W/(m 2 ·K), while those were respectively 1.4 W/(m 2 ·K) and 1.5 W/(m 2 ·K) for the TW and CW system. Throughout a year, the TW system reduced the overall thermal load by 13.6% compared to the CW system with an annual energy collected of 20.3 kWh, while in the WBTW system the corresponding value reached up to 42.6% with an annual energy harvested of 435.7 kWh. Therefore, the WBTW system is an efficient alternative compared to the TW system because it can not only achieve the favorable insulation performance in winter but allow the undesired solar radiation to heat the water in summer and transition seasons.